Impact of Stroke on Caregiver Burden and Quality of Life: A Cross-sectional Study at BMC Hospital, Quetta - Nasar, Abdul Bari; Ihsan ul Haq; Kakar, Amanullah; Qahir, Muhammad; Khaliq, Abdul; Essa, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Stroke imposes significant long-term disability, shifting substantial care responsibilities to informal family caregivers, often leading to considerable burden and reduced quality of life. This study aimed to assess caregiver burden and quality of life among caregivers of stroke patients in Quetta, Pakistan, and identify associated demographic, clinical, and social support factors. Methods: A cross-sectional, hospital-based quantitative study was conducted at Bolan Medical College Hospital, Quetta, involving 689 primary stroke caregivers. Data were collected using the Zarit Burden Interview (ZBI), the WHOQOL-BREF, the Barthel Index, the Mini-Mental State Examination (MMSE), and the Social Support Questionnaire (SSQ). Statistical analyses included descriptive statistics, Spearman’s correlation, independent t-tests, one-way ANOVA, multiple linear regression, and binary logistic regression. Results: The mean ZBI score was 42.7±10.8, indicating moderate to high burden, while the mean WHOQOL-BREF score was 58.4±12.5, suggesting moderate quality of life. Higher caregiver burden was strongly negatively correlated with quality of life (ρ=−0.60,p<0.001) and social support (ρ= −0.56,p<0.001). Key predictors of increased burden included higher stroke severity (β= +0.41,p<0.001), more daily care hours, and lower patient functional and cognitive status. Female caregivers (OR = 1.89), those with low social support (OR = 2.74), longer caregiving time (>8 hrs/day), and low income (<20,000 PKR) were at significantly higher risk of high burden. Conclusion: Informal stroke caregivers in Quetta experience considerable burden with a negative impact on their quality of life, driven by patient dependency, caregiver characteristics, and socioeconomic factors. Enhanced social support is a critical protective factor. These findings underscore the urgent need for targeted interventions to support stroke caregivers in similar settings.